EAACI statement on the diagnosis, management and prevention of severe allergic reactions to COVID‐19 vaccines - Sokolowska, Milena; Eiwegger, Thomas; Ollert, Markus; Torres, Maria J.; Barber, Domingo; Del Giacco, Stefano; Jutel, Marek; Nadeau, Kari C.; Palomares, Oscar; Rabin, Ronald L.; Riggioni, Carmen; Vieths, Stefan; et al. (Allergy (Copenhagen), 2021)
The first approved COVID‐19 vaccines include Pfizer/BioNTech BNT162B2, Moderna mRNA‐1273 and AstraZeneca recombinant adenoviral ChAdOx1‐S. Soon after approval, severe allergic reactions to the mRNA‐based vaccines that resolved after treatment were reported. Regulatory agencies from the European Union, Unites States and the United Kingdom agree that vaccinations are contraindicated only when there is an allergy to one of the vaccine components or if there was a severe allergic reaction to the first dose. This position paper of the European Academy of Allergy and Clinical Immunology (EAACI) agrees with these recommendations and clarifies that there is no contraindication to administer these vaccines to allergic patients who do not have a history of an allergic reaction to any of the vaccine components. Importantly, as is the case for any medication, anaphylaxis may occur after vaccination in the absence of a history of allergic disease. Therefore, we provide a simplified algorithm of prevention, diagnosis and treatment of severe allergic reactions and a list of recommended medications and equipment for vaccine centres. We also describe potentially allergenic/immunogenic components of the approved vaccines and propose a workup to identify the responsible allergen. Close collaboration between academia, regulatory agencies and vaccine producers will facilitate approaches for patients at risks, such as incremental dosing of the second injection or desensitization. Finally, we identify unmet research needs and propose a concerted international roadmap towards precision diagnosis and management to minimize the risk of allergic reactions to COVID‐19 vaccines and to facilitate their broader and safer use.